PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, KEPEMILIKAN INSTITUSIONAL DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK (Studi Empiris Perusahaan Pertambangan yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020) - Dhinda Nuramalia, (2021)
This research is a quantitative research that aims to analyze the influence of corporate social responsibility disclosure, institutional ownership and profitability on tax aggressiveness. This study uses the population of mining companies listed on the Indonesia Stock Exchange in 2016-2020. Using purposive sampling techniques, multiple linear regression methods using STATA V.16 applications, this study did not succeed in proving the effect of corporate social responsibility disclosure, institutional ownership and profitability on tax aggressiveness. This research has implications that in mining companies, especially during the research period, manager activities related to their responsibility to the environment and society are not oriented towards corporate taxes, but properly patterned attention to the sustainability of the company's operations, as well as owners from institutions monitoring and controlling managers on strategic aspects other than corporate tax. From the results of this research, it is also proven that corporate perofitability is not something that can encourage managers to conduct tax avoidance activities, especially during the pandemic period where there are many incentives and policies issued by the Director General of Taxation to encourage the economic sustainability of taxpayers.